Studi Kelayakan Pemanfaatan Pembangkit Listrik Kincir Air Terapung Di Desa Ella Hilir Kecamatan Ella Hilir Kabupaten Melawi - Rahmadi, Joni; Yusuf, Ismail; Priyatman, Hendro (ELKHA: Jurnal Teknik Elektro, 2015)
Abstract– Hydroelectric Power Plant (HEPP) use a boost from the water with a specific discharge and dtransformasikan into electricity by generators. River In Rural District of Ella Ella Downstream Downstream Melawi has the potential to be used as energy alternatives, with water flowing speed of 1m / s to 3 m /s. Utilization of Power Plant Feasibility Study Floating In Water Mill Village District of Ella Ella Downstream Downstream Melawi expected to provide an overview as well as a reference for the public and the government about the prospects and benefits are obtained if done on technology implementation or iplementasi floating waterwheel. Based on the lowest current 1 m / s Watermill floating able to produce 533.70 Watt, the highest river currents capable of producing 144,409.90 Watt, a comparison is electricity derived from PT. PLN with a reference group of R1 / 900 where the electricity tariff (TDL) around Rp. 650, - it is not worth the investment, the comparison is electricity derived from the generator, the power specification 1 kVA and price premium / liter Rp. 6.600, - (January 2015) it is well worth the investment Keywords– hydropower, Watermill, Streams, Generator